Оцінка безпеки об’єкта «Укриття» в процесі перетворення на екологічно безпечну систему - Azarov S.I.; Sydorenko V.P.; Zadunay O.S. (General Energy Institute of the National Academy of Sciences of Ukraine, 2019)
The complexity of safe operation of the “Shelter” object (SO) and the availability of data of different qualimetric nature, describing its behavior, necessitate the development of new methods for assessing the safety of object in question, which would enable us to  perform the integration of these data within a single approach. The methodological foundations proposed in this article are based on a systematic approach and fuzzy inference, which allows the use of qualitative and quantitative data on the object of analysis. It is proposed to make decisions with taking into account the significance of all aspects relative to each other and to quantify the decision options using an approach based on the method of hierarchy analysis, which enables us to determine the safe state of the SO. We present the categories of SO operating conditions, initial events of accidents at the object with the frequency of their occurrence, priority tasks to ensure the security of the specified object, as well as  basic requirements of safety criteria and the principles of their classification. The general safety criteria in the process of converting the SO into an environmentally friendly system are considered in detail, including criteria for nuclear safety, radiation safety, environmental safety, and fire and explosion hazard. It is noted that the quantitative analysis of SO safety with using the above safety criteria is possible only on the basis of objective measurement and prediction of the consequences of hazard. The main elements of level of the potential danger included in the analysis system and principles of the formation of SO safety parameters are indicated. The steps of process of assessing initial events during the analysis of probability of accidents at the SO and the stages of calculation al-and-analytical studies of the occurrence and development of accidents at this facility are listed. The stages of process of the decision-making support for the prevention of accidents and minimization of environmental consequences, as well as the decision-making matrix in emergency situations based on expert assessments are given.